Effect of ultrasound⁃guided intertransverse process block on postoperative analgesia in patients undergoing laparoscopic cholecystectomy - CHEN Qian*，ZENG Yang，ZHU Jixiang，DU Haiyun，QIAN Bin (Zhongguo linchuang yanjiu)
Objective To explore the safety and efficacy of ultrasound-guided inter transverse process block（ITPB）for postoperative analgesia among patients undergoing laparoscopic cholecystectomy（LC）. Methods The research included60 patients scheduled for LC at Yancheng No.1 People’s Hospital from July to September 2024. Participants were randomly divided into ITPB group（group I）and general anesthesia control group（group C）with 30 cases each by digital table method. Both groups were given general anesthesia. After sedation and analgesia, group I received ultrasound ⁃guided ITPB with bilateral single point injection of 25 mL 0.3% ropivacaine before anesthesia induction. Group C did not undergo blocking operations. Intraoperative remifentanil and opioid consumption within 24 hours after surgery were recorded. NRS scores of abdominal incision pain and visceral pain were observed immediately after extubation（T0）, 5 min（T1）, 10 min（T2）, 20 min（T3）, 30 min（T4）, 1 h（T5）, 2 h（T6）, 6 h（T7）, and 24 h（T8）after operation. The first time of getting out of bed and the occurrence of adverse reactions were recorded. Results Compared with group C, group I had a significantly decrease in the intraoperative use of remifentanil and the consumption of opioids in 24 hours after operation（P<0.05）. NRS scores of abdominal incision pain at T1, T2, T7 and visceral pain at seven time points expcept T4 and T6 in group I were lower than those of group C（P<0.05）. Compared with group C, group I had earlier time to get out of bed and lower opioid consumption at 24 hours after surgery（P<0.05）. There was no statistically significant difference in the use of sufentanil in PACU and the occurrence of adverse reactions between the two groups（P>0.05）. Conclusion ITPB has good safety and exact analgesic effects after LC and has good clinical application value.